A new method for quantifying accommodation parameters based on objective dynamic accommodometry - E. P. Tarutta; P. V. Luzhnov; N. A. Tarasova; G. A. Markossian; S. E. Kondratova; L. A. Shamkina (Российский офтальмологический журнал, 2024)
Purpose: to develop a technique for an objective multifactorial assessment of accommodation parameters, including accommodation stability and microfluctuations (MF), and an assessment of the diagnostic value of the technique. Material and methods. The dynamic monocular accommodative response (MAR) was measured using a WAM-5500 device (Grand Seiko, Japan) over a period of 10 to 60 seconds with a recording frequency of at least 6 Hz. The approximating cubic spline was calculated, and the temporal change of signal trend was assessed. The developed technique was used to evaluate the dynamics of MAR for 46 eyes of 23 patients aged 8–12 years with acquired myopia from -0.87 to -5.75 D (ave. -2.96 D). Results. In the examined eyes, the MF frequency varied from 0.4 Hz to 2.3 Hz (ave. 1.4 Hz), and the maximum amplitude ranged from 0.4 D to 2.47 D (ave. 1.2 D). Over the research period, the MAR trend remained constant in 10 eyes, increased from 0.17 to 0.47 (ave. 0.29 D) in 8, and decreased from 0.1 to 1.53 D (ave. 0.35 D) in 28 eyes. MAR varied from 0.79 to 2.63 (ave. 1.8 D). A correlation was found between the minimum MAR and the signal range with the trend level (r= 0.29 and r=0.4, respectively) and a weak correlation was revealed between the MF frequency and the signal range (r=0.2). A set of criteria for accommodation instability was identified: a decreasing trend of more than 0.35 D, a MF frequency of more than 1.4 per second and/or a maximum signal span of more than 1.2 D. Conclusion. The developed technique or objective multifactorial assessment of accommodation parameters, including stability and MF, in real time and space proves to be useful for the diagnosing of accommodation disorders.